2021
DOI: 10.1038/s41467-021-22129-9
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes originating from evolutionary conserved L1 elements interfere with neuronal gene expression in Alzheimer’s disease

Abstract: DNA sequences containing consecutive guanines organized in 4-interspaced tandem repeats can form stable single-stranded secondary structures, called G-quadruplexes (G4). Herein, we report that the Polycomb group protein BMI1 is enriched at heterochromatin regions containing putative G4 DNA sequences, and that G4 structures accumulate in cells with reduced BMI1 expression and/or relaxed chromatin, including sporadic Alzheimer’s disease (AD) neurons. In AD neurons, G4 structures preferentially accumulate in lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 99 publications
0
23
0
Order By: Relevance
“…TE promoters could also serve as alternative promoters yielding chimeric transcripts due to the sense and antisense promoters present in the 5′UTR of LINE‐1 initiating bidirectional transcription [179]. It was recently shown that G‐quadruplexes originating from evolutionarily conserved LINE‐1 elements interfere with neuronal gene expression in AD [181]. Some of these mechanisms through which TEs can alter host gene expression are illustrated in Fig.…”
Section: Tes As Potential Pathogenic Driversmentioning
confidence: 99%
“…TE promoters could also serve as alternative promoters yielding chimeric transcripts due to the sense and antisense promoters present in the 5′UTR of LINE‐1 initiating bidirectional transcription [179]. It was recently shown that G‐quadruplexes originating from evolutionarily conserved LINE‐1 elements interfere with neuronal gene expression in AD [181]. Some of these mechanisms through which TEs can alter host gene expression are illustrated in Fig.…”
Section: Tes As Potential Pathogenic Driversmentioning
confidence: 99%
“…This result suggests that G4 structures alter gene expression and are drastically reduced in AD neurons by more tightly compacting heterochromatin. 67 …”
Section: The Role Of the G-quadruplex In Neurologymentioning
confidence: 99%
“…This dataset [28], which is denoted as dataset 3 (i.e., k = 3) in this study, was composed of eight samples, four of which were AD cell lines and the other four of which were normal cell lines. Because four AD cell lines were composed of two sets of two samples using two distinct cell lines, in this study, this data set is treated as including three categorical classes when coincidence with singular value vectors or latent variables were investigated; two samples were taken from the first AD cell line, two samples were taken from the second AD cell line, and four samples were taken from normal cell lines.…”
Section: Data Set 3: Gse162873mentioning
confidence: 99%